Enhancing maternal well-being, parenting, and toddler's development : findings from a home visitation program - Buğan Kısır, Burcu. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2023., 2023)
The first years of life have been suggested as times of greatest vulnerability and a unique opportunity in terms of development. The accumulating evidence suggested that early adversity compromises young children’s development (Shonkoff et al., 2012). Nurturing and stimulating early care, on the other hand, acts to promote socioeconomically disadvantaged children’s development. This, indeed, underscores the importance of early childhood interventions (Duncan et al., 2012). The first aim of this study was to investigate the role of a home visitation (HV) program entitled The Family Guidance Program, on various familial and developmental outcomes. Going beyond the extant research, this study also aims to delineate mechanisms through which the HV program plays a role in child development in infancy and toddlerhood. Specifically, maternal self-efficacy and developmentally supportive parenting in the first year of child’s life would be examined as intermediary pathways through which the HV program may benefit child development (i.e., general development, expressive language, aggressive behavior, and social competence). The results indicated that the HV program enhanced developmentally supportive parenting, the home environment quality, and infant’s general development (marginally) during the first year of child’s life. Further, as hypothesized, maternal parenting behaviors mediated the role of the HV program on most of the child outcomes at 12 and 18 months of child’s age. The results were discussed in relation past literature and the theory of change the HV program adopted.
Keywords: Child mental health services.; Child and parent.